MUSEUMS - A FOUNDATION FOR THE DEVELOPMENT OF THE SPIRITUAL LIFE OF THE NATION - Sultonova Nigina (Bright Mind Publishing, 2025)
This article examines the history of the formation of the Bukhara State Museum-Reserve, its rich cultural heritage, and its role in preserving and promoting the art of gold embroidery. The study analyzes the museum’s early development, the process of collecting scientific and ethnographic materials, and the features of traditional Bukhara garments. Particular attention is given to the importance of museums in educating the younger generation in the spirit of respect for national heritage.
Keywords: Bukhara, museum-reserve, cultural heritage, gold embroidery, ethnography, traditional clothing, Great Silk Road.